Satellite Communications Modulation and Multiplexing - Thompson, Paul T. (Handbook of Satellite Applications, 2017)
This chapter addresses the principles involved in three key areas in satellite communications, namely, modulation (and demodulation), forward error coding, and multiple access approaches or techniques. It focuses on features and technical approaches utilized in modern-day digital satellite communications systems. Since analog approaches or techniques are today seldom used in operating satellite networks, they are not addressed in detail. Nevertheless, several references are given concerning such analog techniques should there be a historical interest in these subjects. The materials provided in this chapter are aimed at giving an appreciation of the issues involved and the performance achievable in practice. For more detailed mathematical treatments, an extensive bibliography is also provided.